Will customers adopt last-mile drone delivery services? An analysis of drone delivery in the emerging market economy - Charlie Chen; Steve Leon; Peter Ractham (Cogent Business & Management, 2022)
Drone delivery services are novelty concepts to most people in emerging market economies. To gain competitive advantages, retailers in emerging market need to be proactive in understanding the key factors contributing to the acceptance of last-mile drone delivery services by general users. This study offers personal and social perspectives of the adoption of drone delivery services by Thai users. A total of 391 respondents participated in an online survey. The PLS-SEM method was used to perform the data analysis. The analysis results show that personal innovativeness and opinion passions are antecedents for Thai users' perceived ease of use. However, these two antecedents do not affect Thai users' perceived usefulness for drone delivery services. In addition, perceived privacy risk has a negative moderating effect on the relationship between PEOU and the adoption of drone delivery services. In contrast, Thai users' perceived privacy risk has no significant moderating effect on the relationship between PU and the intention to adopt drone delivery services. Lastly, PEOU has a significant positive effect on the intention of users to adopt drone delivery services, whereas PU does not have any significant effect. These findings provide theoretical and practical implications on the moderating effect of perceived privacy risks on the relationships between perceptions and the intention to adopt the last-mile drone delivery service.
Keywords: 650; E-Commerce; emerging market; Drone delivery service; last mile e-commerce